Technologies for Sharing: lessons from Quantified Self about the political economy of platforms. Issue 4 (2nd April 2016) - Barta, Kristen; Neff, Gina
ABSTRACT: Quantified Self (QS) is a group that coordinates a global set of in-person meetings for sharing personal experiences and experiments with self-tracking behaviours, moods, and activities. Through participation in US-based QS events and watching online QS presentations from around the globe, we identify a function of ambiguous valuation for supporting sharing communities. Drawing on Stark's (2011 ) theory of heterarchy, we argue that the social and technical platforms supporting sharing within the QS community allow for multiple, sometimes conflicting, sets of community and commercial values. Community cohesion benefits from ambiguity over which values set is most important to QS members. Ambiguity is promoted by sharing practices through at least two means, the narrative structure of members' presentations, and what counts as tracking. By encouraging members to adhere to a three-question outline, the community ensures that multiple values are always present. Thus, it becomes a question of which values this sharing community emphasizes, not which value sets members present, at any given time. By leaving the tools and methods of tracking open − from sophisticated wearables and data analysis to pen-and-paper and storytelling − the community creates space for and embraces self-trackers with a broad spectrum of technological proficiency and interest. QS as a group capitalizes on circulation of knowledge valued somewhat ambiguously to sustain and grow the community, both encouraging and supporting the commercialization of self-tracking technologies while keeping technology developer interests from overwhelming community-building interests. This, we argue, has implications for researchers hoping to understand online communities and the 'sharing economy' more generally.